The Effect of Internal Motivation and External Motivation on The Performance of Honorary Teachers at State Junior High Schools in Tarowang District, Jeneponto Regency - Ruma, Zainal (PT. Maju Malaqbi Makkarana, 2023)
This research aims to know and explain the effects of internal motivation (X1) and external motivation (X2) on teacher Performance (Y). To figure out the internal motivation influence (X1) partially towards the teacher's performance (Y) and external motivation influence (X2) partially towards the teacher's performance (Y). This research was conducted at SMP Negeri di Tarowang Kabuaten Jeneponto Sub-district. The population and samples in this study are all honorary teachers at SMP Negeri in Tarowang Sub-district of Jeneponto district amounting to 34 people. The data collection techniques are done by providing questionnaires and observations. The data analysis technique used is multiple linear regression through the SPSS 21 application. External motivation to the performance of the honorary teachers had a very strong relationship. The results of multiple linear regression analyses showed that the contribution given by internal motivation and external motivation to the performance of the honorary teacher of the state Junior high School in Tarowang sub-district of Jeneponto was 63%.